Improvement of Mechanical Properties of Noil Hemp Fiber Reinforced Polypropylene Composites by Resin Modification and Fiber Treatment - Zili Yan; Jianchun Zhang; Hua Zhang; Hao Wang (Advances in Materials Science and Engineering)
The present study aims to improve the reinforcement of hemp fibre to polypropylene (PP) by simple resin modification and fibre treatment. Maleic anhydride grafted polypropylene (MAPP) was used as resin modifier by direct mixing with PP, and hydrophobically modified hydroxyethyl cellulose (HMHEC) was used as fibre treatment reagent by immersing fibre into its aqueous solution. The influences of fibre content, resin modification, and fibre treatment on the mechanical properties (tensile, flexural, and impact strengths) of composites were investigated. The change of interfacial bonding between fibre and resin in composites caused by MAPP and HMHEC was studied by scanning electron microscopy and dynamic mechanical analysis. Resin modification and fibre treatment were effective to enhance the mechanical properties of the composites. The improvement in interfacial bonding is quantitatively evaluated with adhesion factor.